Pengaruh Servant Leadership, Budaya Organisasi, Kompensasi Dan Disiplin Kerja Terhadap Kinerja Pegawai ATT Group – Jakarta - Hidayat, Cecep Edi; Muliadi, Muliadi; Wahyudi, Agus; Pujia, Dede Puspa (Universitas Dharmawangsa, 2024)
This study aims to determine the magnitude of the influence of servant leadership, organizational culture, compensation, and work discipline on employee performance at ATT Group Jakarta in 2023, either partially or simultaneously. The primary data is used by distributing questionnaires via Google form to respondents. The method used in this study is a quantitative method with a sampling technique using Slovin so that the number of samples in this study is 170 people. The analysis technique used is multiple linear regression analysis using the SPSS (Statistical Package for Social Science) program for window version 25. The t-test results show the t-count value on the servant leadership variable of 0.805, which is smaller than the t-table of 1.974 (0.805 < 1.974) and the sig. 0.422 is greater than 0.05 (0.422 > 0.05), on the organizational culture variable the t-count value is 4.220 greater than the t-table 1.974 (4.220 > 1.974), and the sig. 0.000 is smaller than 0.05 (0.000 <0.05), in the compensation variable t-count 1.235 is smaller than t-table 1.974 (1.235 <1.974), and the sig. 0.219 is greater than 0.05 (0.219 > 0.05), for the work discipline variable the t-count value is 6.679 is greater than the t-table 1.974 (6.679 > 1.974), and the sig. value is 0.000 less than 0.05 (0.000 < 0.05 ), then from the results of the hypothesis test, it can be stated that partially servant leadership and compensation have no significant effect on employee performance. In contrast, the variables of organizational culture and work discipline have a positive and significant effect on employee performance. The results of the F test showed that F-count is 68.062 greater than F-table 2.426 (68.062 > 2.426) and a significance value of 0.000 is less than 0.05 (0.000 <0.05) so it can be stated that servant leadership, organizational culture, compensation, and work discipline simultaneously / jointly has a positive and significant effect on the performance of ATT Group Jakarta employees.. Abstract ditulis dalam satu alinea, tidak lebih dari 250 kata. (Times New Roman 11, spasi tunggal, dan cetak miring).